Gerakan Sosial Keagamaan pada Komunitas Urban: Studi Kasus Gerakan Pengajian Ahad Pagi Bersama di Palebon, Pedurungan, Kota Semarang - Kusmanto, Thohir Yuli (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
Religious communities express religiously in various forms according to the social context in which they develop. The diversity of the expression as a form of interrelations of textual interpretation of the social context and its era. Religious social movement is one form of religious expression to answer complex religious and social issues and needs from primary to tertiary needs. The urban community utilizes religious social movements in the form of majelis taklim. Organizing religious social movements in majelis taklim is part of collective awareness and consensus among community members. The existence of religious social elites is the key to achieving religious social movements. The trust and social network of citizens and social institutions become another force within the community. In the case of this study, the religious social movements of urban communities take the form of routine recitation activities, the collection of zakat infaq and shadaqah, the organization of formal education, community health services, and the development of economic enterprises. In this social movement, the basic problems faced include the capacity of management and human resources. The implications of the presence of religious social movements in urban communities are felt. They have a spirit of unity on the basis of trust in the community, fulfilled the religious social needs and awakened the identity of the community that has the advantage.Â